Efficacy of a Drug-Eluting Stent Versus Bare Metal Stents for Symptomatic Femoropopliteal Peripheral Artery Disease: Primary Results of the EMINENT Randomized Trial. Issue 21 (18th October 2022) - Gouëffic, Yann; Torsello, Giovanni; Zeller, Thomas; Esposito, Giovanni; Vermassen, Frank; Hausegger, Klaus Armin; Tepe, Gunnar; Thieme, Marcus; Gschwandtner, Michael; Kahlberg, Andrea; Schindewolf, Marc; Sapoval, Marc; et al.
Abstract : Background: A clear patency benefit of a drug-eluting stent (DES) over bare metal stents (BMSs) for treating peripheral artery disease of the femoropopliteal segment has not been definitively demonstrated. The EMINENT study (Trial Comparing Eluvia Versus Bare Metal Stent in Treatment of Superficial Femoral and/or Proximal Popliteal Artery) was designed to evaluate the patency of the Eluvia DES (Boston Scientific, Marlborough, MA), a polymer-coated paclitaxel-eluting stent, compared with BMSs for the treatment of femoropopliteal artery lesions. Methods: EMINENT is a prospective, randomized, controlled, multicenter European study with blinded participants and outcome assessment. Patients with symptomatic peripheral artery disease (Rutherford category 2, 3, or 4) of the native superficial femoral artery or proximal popliteal artery with stenosis ≥70%, vessel diameter of 4 to 6 mm, and total lesion length of 30 to 210 mm were randomly assigned 2:1 to treatment with DES or BMS. The primary effectiveness outcome was primary patency at 12 months, defined as independent core laboratory–assessed duplex ultrasound peak systolic velocity ratio ≤2.4 in the absence of clinically driven target lesion revascularization or surgical bypass of the target lesion. Primary sustained clinical improvement was a secondary outcome defined as a decrease in Rutherford classification of ≥1 categories compared with baseline without a repeat target lesion revascularization. Health-related quality of life and walking function were assessed. Results: A total of 775 patients were randomly assigned to treatment with DES (n=508) or commercially available BMSs (n=267). Baseline clinical, demographic, and lesion characteristics were similar between the study groups. Mean lesion length was 75.6±50.3 and 72.2±47.0 mm in the DES and BMS groups, respectively. The 12-month incidence of primary patency for DES treatment (83.2% [337 of 405]) was significantly greater than for BMS (74.3% [165 of 222]; P <0.01). Incidence of primary sustained clinical improvement was greater among patients treated with the DES than among those who received a BMS (83.0% versus 76.6%; P =0.045). The health-related quality of life dimensions of mobility and pain/discomfort improved for the majority of patients in both groups (for 66.4% and 53.6% of DES-treated and for 64.2% and 58.1% of BMS-treated patients, respectively) but did not differ significantly. At 12 months, no statistical difference was observed in all-cause mortality between patients treated with the DES or BMS (2.7% [13 of 474] versus 1.1% [3 of 263]; relative risk, 2.4 [95% CI, 0.69–8.36]; P =0.15). Conclusions: By demonstrating superior 1-year primary patency, the results of the EMINENT randomized study support the benefit of using a polymer-based paclitaxel-eluting stent as a first-line stent-based intervention for patients with symptomatic peripheral artery disease attributable to femoropopliteal lesions. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02921230.